A descriptive analysis of drivers under the influence of opioids in Kentucky. (December 2022) - Dickson, Megan F.; Kissel, Megan; Shore, Stephen; Matthew Webster, J.
Highlights: This study examines drivers under the influence of opioids (DUIOs). DUIOs are more common in rural areas. DUIOs are more likely to report driving under the influence of multiple substances. Other substance involvement among DUIOs varies by rurality. Abstract: Despite the ongoing opioid epidemic and evidence of the increasing prevalence of driving under the influence of opioids, particularly in rural communities, there remains a limited understanding of those who drive under the influence of opioids. The current study aims to fill this gap in the literature by examining drivers under the influence of opioids (DUIOs) using the clinical substance use assessment records of a statewide sample of drivers convicted of driving under the influence (N = 15, 917); first identifying differences between DUIOs and drivers under the influence of other, non-opioid substances, followed by an examination of factors associated with driving under the influence of opioids in combination with other substances, and finally, comparing rural and urban DUIOs (N = 1, 571). Bivariate analyses were used to compare groups, while a logistic regression model was used to identify correlates of other substance involvement. DUIOs differed from drivers under the influence of other, non-opioid substances, such as being more likely to be convicted in a rural community (65.7% vs 53.6%) and to be under the influence of multiple substances at the time of arrest (42.0% vs 7.1%). Among DUIOs, a rural conviction ( p  =.016) and meeting DSM criteria for an alcohol ( p  <.001) and drug use disorder ( p  <.001) were positively associated with driving under the influence of opioids in combination with other substances. Results also highlighted a number of differences between rural and urban DUIOs, including other substance involvement. Urban DUIOs were more likely to report alcohol involvement in their DUI arrest (16.7% vs 9.1%), and rural DUIOs were more likely to report other, non-opioid drug involvement (36.9% vs 29.1%). Results suggest a possible need for different prevention and treatment approaches depending on rural/urban environment, which is noteworthy given limited treatment availability and other barriers to substance use treatment in rural communities.